Surface Roughness of Artificial Teeth after Immersion in Coffee Solution and Denture Cleaning - Nursyahbani, Nana Wafiqah; Yunisa, Fahmi; Sari, Nurfita (Applied mechanics and materials, 2022)
Artificial teeth are components in removable partial dentures or complete dentures. The denture will be exposed to various liquids from food and beverages in daily use. On the other hand, dentures should also be cleaned regularly with various cleaning methods, either mechanically or chemically. Exposure to various things can result in changes in the surface structure of artificial teeth. The purpose of this study was to evaluate the surface roughness of the denture elements that had been exposed to coffee and then cleaned mechanically and chemically. A total of 30 artificial teeth were immersed in the coffee solution for 2.5 days in an incubator at 37 ° C. Then, the samples were divided into three groups (n = 10) according to the cleaning treatment. Group A was cleaned mechanically using an electric toothbrush and toothpaste for 2 minutes, group B was cleaned chemically by soaking in a solution of alkaline peroxide for 3 minutes, and Group C was the control group and cleaned through immersion in distilled water for 3 minutes. All samples were measured for surface roughness before and after immersion in coffee solution and after cleaning treatment using a Profilometer (Surfcorder SE 1700). Data were analyzed using a paired-sample t-test and ANOVA. The surface roughness of artificial teeth (3.62 µm) increases to 4.092 µm after immersion in coffee solution (p<0.05). After the denture cleaning procedure was carried out, although group B show the highest values (3.32 µm), but the difference in the mean surface roughness between the cleaning treatment groups did not show a significant difference (p> 0.05). As the conclusion, the denture cleaning method in this study (mechanical and chemical) did not give negative results on the surface roughness of the artificial teeth that had been exposed to the coffee solution.